Foreign exchange exposure and multinationality - Hutson, E.; Laing, Elaine (Elsevier BV, North Holland, 2014)
We examine the relation between firms’ foreign exchange exposure and the extent of their multinationality as a proxy for operational hedging. Using a sample of 953 US firms over the period 1999–2006, we show that there is a nonlinear relation between operational and financial hedging, confirming anecdotal evidence that many highly multinational firms do not hedge with derivatives. We find that operational hedging and financial hedging are significantly inversely related to firms’ foreign exchange exposure, providing evidence that the two hedging techniques are complementary for all but the most highly operationally hedged firms. By comparing our findings for 1999–2006 with 1999–2009, we show that this complementarity breaks down when exchange rate volatility is high – as the effectiveness of financial hedging diminishes. An important message for firms is that operational hedges work, and they potentially provide better protection than financial hedging during times of stress.